IPR protection and optimal entry modes of multinationals - Tanmoyee Banerjee; Nilanjana Biswas (Kiel Institute for the World Economy (IfW), 2016)
The present paper develops a model to analyze the relationship between modes of entry of a Multinational Corporation (MNC) in a vertically differentiated market in a Less Developed Country (LDC) to the Intellectual Property Rights (IPR) protection policy adopted by the LDC government. The MNC has two options of entry: fragment production structure and shift assembling unit to LDC, or shift entire production to LDC with full technology transfer. The MNC incurs investment to control the copying of the original product by a commercial pirate in the two modes of entry. The results show that the optimal anti-copying investment is inversely related with the IPR protection rate chosen by the LDC government. The government may or may not monitor in equilibrium. However, government monitoring may not result in complete deterrence of piracy. Further, the MNC shifts complete production to LDC with full technology transfer if the transport-cost of sending semi-finished product from developed country to LDC is above a critical level, otherwise a fragmented mode of entry takes place with assembly-line FDI in LDC.
Keywords: L11; O33; O34; O38; 330; assembly line FDI; FDI with technology transfer; piracy; IPR protection